Avaliação dos impactos na estabilidade global em estruturas de concreto armado com o aumento do gabarito das edificações em Fortaleza - Leite, Maria Thereza Assunção Furtado (2018)
The analysis of global stability in reinforced concrete buildings is a major study subject in view of the increase in population density and the urban and architectural requirements of increasingly high and slender buildings in large cities, especially for the buildings in Fortaleza, in view of the increase of the maximum allowed hight of buildings proposed in the Land use and Occupation Law (LUOS, 2017). The objective of this work is to evaluate the influence of the change of compressive strength of the concrete and the modification of the dimensions of columns, uniformly and gradually, in the gamma-Z parameter of global stability of buildings of usual structural design in Fortaleza. Thus, the rating s given through structural analysis, with the commercial software CAD/TQS, of two buildings, alternating the values of the high of the building in between 30 and 45 floors for each structure, analyzing the effects of the change of compressive strength of the concrete (fck), of the sections of the columns and their geometric design, besides the inclusion and exclusion of other columns in the increase or decrease of the gamma-z parameter. The results show that there is a direct influence of the increase of the fck and the moment of inertia of columns in the decrease of gamma-z parameter, but that this interference tends to stabilize as the structure becomes more rigid, and other actions are needed, such as the inclusion of rigid cores and concrete walls, to achieve a safer level of stability